Morphology, Chemical Composition and Medical Use of Ocimum Plant (Texas Journal of Agriculture and Biological Sciences, 2023)
In this article, the morphology of basil plant, propagation ecology, agrotechnical measures, preparation of raw materials and its quality, use in medicine and folk medicine, chemical composition and recommendations on the use of the plant are highlighted. Today, traditional medicine (folk medicine) is a very rich and vast body of experience and knowledge, imbued with folk ingenuity. It is an inexhaustible resource that enriches scientific (official) medicine with new, effective medicinal preparations. The value and role of folk medicine in this field is priceless. For this, as an example, it is enough to remember that most of the medicinal plants used in modern medicine were taken from the treasury of folk medicine in a short period of time, or that modern scientific medicine developed on the basis of folk medicine.